GAMBARAN HASIL PEMERIKSAAN OTOAKUSTIK EMISI (OAE) SEBAGAI SKRINING AWAL PENDENGARAN PADA BAYI BARU LAHIR DI RSU ROYAL PRIMA MEDAN - Jessica Anne Girsang; Safrianto Safrianto; Yuliani Mardiati Lubis; Sri Wahyuni Nasution (Jurnal Darma Agung, 2022)
Hearing loss in newborns can affect speech, language, and cognitive development. OAE is an examination technique that looks at the function of the cochlea by looking at the deep acoustic response of the outer hair cells to sound stimulation. The purpose of this study was to provide an overview by investigating her OAE at the newborn hearing screening at RSU Royal Prima Medan. This study is a cross-sectional design descriptive study conducted at RSU Royal Prima Medan. From September to October 2022, 15 newborns were examined. The results of this study found that the majority of those who did OAE examinations were infants aged 0-24 hours totaling 9 babies (60%), based on gender, 10 (66.7%) women, 5 (33.3%), based on gestational age. Mothers obtained term 13 (86.7%) very premature 2 (13.3%), based on normal BBL 13 (86.7%) low 2 (13.3%), based on the type of delivery by caesarean section 12 (80%) normal 3 (20%), based on examination of right ear OAE pass 13 (86.7%) refer 2 (13.3%), based on examination of left ear OAE pass 12 (80%) refer 3 (20%). It can be concluded that OAE examination needs to be done as an initial hearing screening in newborns for early detection of hearing loss.